Efficiency of solar PV panel by the application of coconut fibres saturated by earthen clay pot water. Issue 3 (28th January 2021) - Rajasekar, R.; Prasannaa, P.; Ramkumar, R.
ABSTRACT: Performance of the solar cell is hindered at higher operating temperature. Although higher irradiation increases the yield annually, the higher temperature would do a disservice. As temperature increases, the solar cell undergoes a thermal stress owing a way to carrier recombination. It becomes imperative to ease of the thermal stress, thereby running the PV system effectively and achieving the higher yield. An alternative cooling method is applied by cooling both the sides of the PV panel simultaneously. It includes cooling of the panel top surface by allowing a thin film of water to flow. The rear surface is packed with a biomaterial, which is saturated with the constant supply of water. This makes up a cooling unit. Here, the experimental study is carried out on comparison between a conventional PV panel and PVT panel packed with coir pith at the rear surface. The latter is cooled at two different modes, one among the panel by normal water and the other by earthen pot water. The results show that cooling the coir pith using earthen pot water has increased the overall efficiency up to 64%. It is higher than the other two panels, as the temperature of the pot water is 5°–8°C lower than the ambient air. GRAPHICAL ABSTRACT: UF0001